Kérdőjelek és hiányjelek a tanyakutatásban - Timár, Judit (Tér és Társadalom, 1990)
Scattered farmstead (tanya) is a specific element in the Hungarian settlement pattern. Eacl major period of its development left marked changes on its essential features. At the beginniN it served as shepards’ accomodation. In its golden age it became an agricultural centre. Its inha bitants, as citizens of rural market towns, were attached to the town by highly intensive relation ships. By the 1960s, it became the accomodation of workers oflarge-scale socialist farms. Toda: it is again in a new socio-economic situation. Depending on future changes, it can either be come a slum or a modern farm. Its position within the settlement-, economic- and social system should be reconsidered. What is at all to be considered as a tanya–is an issue for discussion. In the case of tanyas the unity of places of home and work cannot be a criterion of the settle ment. These functions are spatially so much apart that the settlement itself can no longer identified on that basis. It is the morphological features (loosely built-up area, low populatioi density, long distances) that define a scattered farmstead region. By gradual „densification" however, this very feature is decreasing on the long run. The major distinction between tanya and most other European scattered settlements is tha here mainly only household or auxiliary farming is done. And this is the tanya’s intrinsic fea ture. It is possible that this is the only economic function to strengthen in the filmre. People living in tanyas can no longer be exclusively identified as workers of large-scal( farms: more than 40 % of them no longer work in agriculture. Their living environment is however, still very much underprivileged. They are, still today, intensively linked to the paren settlement by their social links but relationships can also be significant among tanyas them selves and with other settlements. The building up of genuine local governments would, hope fully, improve the situation of tanya population and may also modify the direction of its spatia links. The most important features of conceptual criteria of the tanya are therefore the scattered character, the private-, household- or auxiliary farming, a relatively large rural population and a specific history and development path.